Factors of bankruptcy in Malaysia / Norehan Ahmad Nasir - Ahmad Nasir, Norehan (2018)
Research reported in this paper is a research on “Factors that Leads to Bankruptcy in Malaysia”. The aim of this research is to investigate the relationship of credit card rate, medical debt rate and personal debt rate to the number of bankruptcy recorded in Malaysia. The research used Autoregressive Distributed Lag (ARDL) in order to find the relationship among those independent variables to the number of bankruptcy cases in Malaysia. The quarterly rates were collected from quarter 1 in 2006 to quarter 2 in 2013.The result of this study show that credit card and medical debt have significant relationship to the number of bankruptcy. As conclusion for the studies shows that the credit card, medical debt and personal debt become are factors that contribute to the number of bankruptcy.